Carotenoid Derivates in Achiote (Bixa orellana) Seeds: Synthesis and Health Promoting Properties - Rivera-Madrid, Renata; Aguilar-Espinosa, Margarita; Cárdenas-Conejo, Yair; Garza-Caligaris, Luz E. (Frontiers in Plant Science, 2016)
Bixa orellana (family Bixaceae) is a neotropical fast growing perennial tree of great agro-industrial value because its seeds have a high carotenoid content, mainly bixin. It has been used since pre-colonial times as a culinary colorant and spice, and for healing purposes. It is currently used as a natural pigment in the food, in pharmaceutical, and cosmetic industries, and it is commercially known as annatto. Recently, several studies have addressed the biological and medical properties of this natural pigment, both as potential source of new drugs or because its ingestion as a condiment or diet supplement may protect against several diseases. The most documented properties are anti-oxidative; but its anti-cancer, hypoglucemic, antibiotic and anti-inflammatory properties are also being studied. Bixin’s pathway elucidation and its regulation mechanisms are critical to improve the produce of this important carotenoid. Even though the bixin pathway has been established, the regulation of the genes involved in bixin production remains largely unknown. Our laboratory recently published B. orellana’s transcriptome and we have identified most of its MEP (methyl-D-erythritol 4-phosphate) and carotenoid pathway genes. Annatto is a potential source of new drugs and can be a valuable nutraceutical supplement. However, its nutritional and healing properties require further study.